The impact of environmental cues on customers' quality perception and willingness to pay, and the moderating role of consumer mood and motives - Marcomini, Silvia (2016)
The literature shows that shopping environment has an impact on various consumer behaviors, and that favourable environmental cues are associated with higher customer’ quality perception and willingness to pay. I investigated and found that this is true only when consumers are in a positive mood. When they are in a negative mood, consumers infer higher quality from a discount-looking shop. A between-design experimental survey has been conducted to analyze the impact of shopping environment, mood and shopping motivation on customers’ perception of quality and willingness to pay. Two mood conditions (positive/negative) have been created and induced to respondents at the beginning of the survey, along with two shopping environment conditions (upscale-looking/discount-looking) based on design, scent and sales personnel factors. Results show that shopping environment does not impact significantly the dependent variables but it interacts significantly with mood to determine quality perception; shopping motivation impacts significantly both quality perception and willingness to pay.